Computer modelling on human telomeric dna g-quadruplexes, from stability, folding dynamics to ligand binding - Luo, Di (2016)
G-quadruplex is a non-canonical yet crucial secondary structure of nucleic acids, which has proven its importance in cell aging, anti-cancer therapies, gene expression and genome stability. In this PhD thesis, we studied the five established structural models of human telomeric DNA G-quadruplexes on their thermal stabilities, folding dynamics and ligand binding behaviours. Firstly, temperature-replica exchange MD simulations were carried out by incorporating the five folding topologies as conformational isomers. The frequencies of folded topologies occurring at low temperature replicas indicate that the structure of hybrid-2 type is the most stable G-quadruplex folding topology. Next, parallel tempering metadynamics simulations in the well-tempered ensemble were performed to study the folding/unfolding dynamics of the hybrid-1 and -2 type G-quadruplexes. A hairpin and a triplex intermediate were identified from the free energy landscape of the hybrid-1 type, which is consistent with current experimental findings. More importantly, flip-overs of the N-glycosidic conformations of guanines were observed in the transition structures. It has been found out that the flip-over is to re-orient the directions of the Hoogsteen H-bond donor and acceptor of a guanine to participate in the cyclic Hoogsteen H-bonding for a new G-tetrad, which is usually but not necessarily accompanied by a conversion between the syn- and anti-conformations. Furthermore, ligand binding behaviours of G-quadruplexes with Thioflavin T (ThT) were investigated via conventional and well-tempered metadynamics (WT-MetaD) simulations. It is found that the five folding topologies of G-quadruplexes are differentiated in their binding modes as well as binding affinities with ThTs. The major binding modes are identified as the end, sandwich and base stacking via π-π interactions. Specifically, the sandwich stacking is triggered by the reversible conformational change on G-quadruplex and facilitated by the collaboration between ligands. Finally, a case study on the +1 nucleosomes of yeast was carried out. By extracting the +1 nucleosome sequences on the coding strand from the yeast genome and analysing the frequencies of occurrence of dinucleotides, it is revealed that the bending-resistant AA dinucleotide is more abundant in the first half of +1 nucleosomes. This result suggests that the unwrapping of +1 nucleosomes for DNA transcription in yeast might be mechanically regulated by positioning the rigid AA dinucleotide at the 5’ end. In summary, the work presented in this thesis provides original insights into the dynamics and folding of G-quadruplexes, which can be utilized by experimentalists to stabilize the structures or to intervene their formation in genome. Besides, the bioinformatics study on the +1 nucleosomes of yeast helps to realize the roles of DNA sequence on gene regulation, which will be further investigated in future work.